CFD Simulation of Liquid–Liquid Two-Phase Hydrodynamics and Axial Dispersion Analysis for a Non-Pulsed Disc and Doughnut Solvent Extraction Column. Issue 6 (18th September 2016) - Yi, Heng; Wang, Yong; Smith, Kathryn H.; Fei, W. Y.; Stevens, Geoffrey W.
ABSTRACT: A two-phase computational fluid dynamics (CFD) simulation for a non-pulsed disc and doughnut solvent extraction column has been developed with commercial CFD software FLUENT. Simulated hydrodynamic results including phase distribution, velocity fields, and holdup are given, which enables predicted holdup to be compared with experimental data. Average absolute relative deviation (AARD) of experimental data and CFD prediction in this study is found to be 10.8%, which is comparable to the estimated error in the experimental data and the predictions from traditional correlations in the literature. To estimate the extent of axial dispersion, a species transport model is used for the continuous phase with a small amount of tracer introduced in the continuous phase, when Sauter mean diameter of the dispersed phase is set to be 3.5 mm. A two-point monitoring method is used to estimate a Peclet number. The tracer concentration distribution in the two-dimensional distance–time space is interpreted with MATLAB along with the experimental measurement. The simulated Peclet numbers are compared with column experiments, and in general the simulation underestimates the experimental data by 60%. Introducing a modified drag law improves the predictions. This work shows that CFD can successfully model the performance of a non-pulsed disc and doughnut solvent extraction column.